When migrant learners are Italian: perceptions of learning support educators on the inclusion of Italians in Maltese schools - Baschiera, Barbara; Caruana, Sandro (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2020)
In this paper we first provide an overview of recent Italian migration to Malta and we then focus our attention on the experiences and perceptions of 42 Learning Support Educators (LSEs) in relation to the inclusion of Italian learners in Maltese secondary, primary and pre-primary schools. Through quantitative findings from a questionnaire and qualitative reflections based on three focus groups we investigate linguistic and socialisation issues, as well as pedagogical practices, and how these lead to the inclusion of Italian nationals in Maltese schools. Results indicate that inclusion in a bilingual schooling system, characterised by the interplay between English and Maltese, presents several challenges for Italian students. While knowledge of English is highly important for their scholastic attainment, Maltese has a fundamental role too especially for socialisation. Problems with language competence also lead to other difficulties. In a system which is often geared towards achieving results in high-stakes examination and in which students are ranked on the basis of achievement, a rethinking of some of the principles that guide education is required, through inclusive pedagogical paradigms based on discovering and giving value to the educational potential of all learners.